Potential Applications and Functional Roles of Exosomes in Cardiometabolic Disease - Sergio Ayala-Mar; Belén Rodríguez-Morales; Pedro Chacón-Ponce; José González-Valdez (MDPI AG, 2021)
Despite diagnostic and therapeutic advances, cardiometabolic disease remains the leading cause of death worldwide. Extracellular vesicles (EVs), which include exosomes and microvesicles, have gained particular interest because of their role in metabolic homeostasis and cardiovascular physiology. Indeed, EVs are recognized as critical mediators of intercellular communication in the cardiovascular system. Exosomes are naturally occurring nanocarriers that transfer biological information in the setting of metabolic abnormalities and cardiac dysfunction. The study of these EVs can increase our knowledge on the pathophysiological mechanisms of metabolic disorders and their cardiovascular complications. Because of their inherent properties and composition, exosomes have been proposed as diagnostic and prognostic biomarkers and therapeutics for specific targeting and drug delivery. Emerging fields of study explore the use exosomes as tools for gene therapy and as a cell-free alternative for regenerative medicine. Furthermore, innovative biomaterials can incorporate exosomes to enhance tissue regeneration and engineering. In this work, we summarize the most recent knowledge on the role of exosomes in cardiometabolic pathophysiology while highlighting their potential therapeutic applications.